Security intelligence : a practitioner's guide to solving enterprise security challenges - Li, Qing, 1971-; Clark, Gregory (Indianapolis, IN : Wiley, 2015)
Identify, deploy, and secure your enterprise Security Intelligence, A Practitioner's Guide to Solving Enterprise Security Challenges is a handbook for security in modern times, against modern adversaries. As leaders in the design and creation of security products that are deployed globally across a range of industries and market sectors, authors Qing Li and Gregory Clark deliver unparalleled insight into the development of comprehensive and focused enterprise security solutions. They walk you through the process of translating your security goals into specific security technology domains, fo.
Extracting URL Feature SetsClassifier Training; Dynamic Webpage Content Rating; Keyword Extraction for Category Construction; Keyword Categorization; Detecting Malicious Web Infrastructure; Detecting Exploit Servers through Content Analysis; Topology-Based Detection of Dedicated Malicious Hosts; Detecting C2 Servers; Detection Based on Download Similarities; Crawlers; Detecting Malicious Servers with a Honeyclient; High Interaction versus Low Interaction; Capture-HPC: A High-Interaction Honeyclient; Thug: A Low-Interaction Honeyclient; Evading Honeyclients; Summary; Chapter 6 Writing Policies
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed April 13, 2015).
Keywords: Electronic information resources -- Access control; Computer networks -- Security measures; Computer security; COMPUTERS / Internet / Security; COMPUTERS / Networking / Security; COMPUTERS / Security / General; Computer networks -- Security measures. World Wide Web -- Security measures; Computer science; Network security; Computer networks -- Security measures; Computer security; Electronic information resources -- Access control; Electronic books; Electronic books